(untitled) (Advances in Civil and Architectural Engineering, 2022)
The indoor climate of industrial buildings is a function of production technology and requirements for the creation of an optimal artificial material environment. Currently, we consider daylight not only as a source of illumination, but also as an aesthetic element of a building or a way of reducing energy consumption. Light in a closed space allows a person to obtain basic visual information (perception) and perform visual tasks. Top lighting schemes can provide increasingly more useful illumination from smaller apertures than side lighting when they capture and diffuse sunlight. Sunlight is roughly 10 times brighter than light from the sky or clouds. A combined lighting system (top lighting and side lighting) ensures a better light distribution in industrial buildings. In this study, we present a comparison of daylight factors for different types of skylights. Specifically, a saddle skylight in the hall and three other types of skylights were created and simulated. In all the cases, the models of skylights were prepared and simulated using RADIANCE. Additionally, a comparison of simulation results obtained with RADIANCE was conducted to quantify the lighting climate. Overall, saddle roof was considered as the best choice for daylight in an industrial hall.